Desenvolvimento e validação de método por cromatografia líquida em fase reversa para análise de febuxostate - Duarte, Marlon Both (2013)
Febuxostat is a novel non purine drug indicated for the treatment of hyperuricemia in gout. A reversed-phase liquid chromatography (RP-LC) method was validated for the determination of febuxostat in pharmaceutical dosage forms. The LC method was carried out on a XTerra C18 column (150 mm x 3.9 mm I.D.), maintained at 25 ºC. The mobile phase consisted of water (pH 3.5) acetonitrile (40:60, v/v), run at a flow rate of 0.8 mL/min and using photodiode array (PDA) detection at 316 nm. The chromatographic separation was obtained with retention time of 3.9 min, and was linear over the range of 0.25 - 30 μg/mL (r2=0.9995). The specificity and stability-indicating capability of the method was proven through degradation studies were carried out by LC and MS and showing also, that there was no interference of the excipients and degradation products in the quantification of the drug. Moreover, the in vitro cytotoxicity test of the degraded products showed significant differences (p<0.05). The accuracy was 100.54% with bias lower than 0.65%. The limits of detection and quantitation were 0.08 and 0.28 μg/mL, respectively. The procedure was validated evaluating parameters such as the specificity, linearity, precision, accuracy, limits of detection and quantitation, robustness, and system suitability test, giving results within the acceptable range. The proposed method was applied for dissolution studies and the analysis of tablet dosage forms, contributing to assure the safety and therapeutic efficacy.